Relations between nitric oxide synthase DNOS1, Hsp70 and apoptosis regulatory gene grim in Drosophila melanogaster after heat stress induction - Khussainova, E.M.; Bulentayeva, Z.A.; Bekmanov, B.O.; Djansugurova, L.B.; Bersimbayev, R.I. (Вiopolymers and Cell, 2010)
Aim. To investigate correlation between nitric oxide synthase, heat shock protein Hsp70 and apoptosis regulatory gene grim in D. melanogaster. Methods. The heat stress (37 C for 1 hour) induction in third instar larvae of Oregon R strain and transgenic strains, containing additional copies of dNOS1 gene. RT-PCR and Western-blot analysis were used to study the expression of dNOS, Hsp70 and grim genes. Results. It is demonstrated that additional copies of dNOS1 gene in transgenic strains are intensively expressed immediately after heat stress induction. It was revealed that in all Drosophila strains the level of Hsp70 gene expression and its protein synthesis increase with subsequent decline after 2–3 hours; whereas the level of expression of grim increases immediately after heat stress induction in transgenic strains and declines in wild type flies, while the level of Hsp70 expression remains high. Conclusions. The increased level of Hsp70 has negative impact on the expression of grim, whereas additional NO synthesis neutralizes anti-apoptotic effects of Hsp70 and increases the expression level of grim. Thus, we assume the competitive relationships between anti-apoptotic functions of Hsp70 and pro-apoptotic effects of nitric oxide. Мета. Дослідити взаємозв’язок між синтазою оксиду азоту, білком теплового шоку (БТШ70) та апоптоз-регулюючим геном grim у D. melanogaster. Методи. Індукція теплового шоку (37 C, 1 год) у личинок 3-го віку лінії Oregon R і трансгенних ліній з додатковими копіями dNOS1-гена. Для аналізу експресії генів dNOS, hsp70 и grim використано методи ЗТ-ПЛР і Вестерн-блот. Результати. Показано, що в трансгенних лініях додаткові копії гена dNOS1 активно експресуються відразу після теплового стресу. Виявлено, що в усіх використаних лініях рівень експресії hsp70 і його білкового продукту підвищується після індукції стресу і знижується через 2–3 год, у той час як рівень експресії гена grim у трансгенних лініях за таких же умов підвищується, а в контролі зменшується при збереженні високого рівня експресії hsp70. Висновки. Значний рівень БТШ70 негативно впливає на експресію гена grim, додатковий синтез NO нейтралізує антиапоптичну дію БТШ70 і підвищує рівень експресії grim. Таким чином, ми передбачаємо наявність конкурентного взаємозв’зку між антиапоптичною функцією БТШ70 і про-апоптичною дією оксиду азоту. Цель. Исследовать взаимосвязь между синтазой оксида азота, белком теплового шока (БТШ70) и апоптоз-регулирующим геном grim у D. melanogaster. Методы. Индукция теплового шока (37 C, 1 ч) у личинок 3-го возраста линии Oregon R и трансгенных линий с дополнительными копиями dNOS1 гена. Для анализа экспрессии генов dNOS, hsp70 и grim использовали методы ОТ-ПЦР и Вестерн-блот. Результаты. Показано, что в трансгенных линиях дополнительные копии гена dNOS1 активно экспрессируются сразу после теплового стресса. Выявлено, что во всех используемых линиях уровень экспрессии hsp70 и его белкового продукта повышается после индукции стресса и снижается через 2–3 ч, в то время как уровень экспрессии grim в трансгенных линиях в этих же условиях возрастает, а в контроле уменьшается при сохранении высокого уровня экспрессии hsp70. Выводы. Значительный уровень БТШ70 негативно влияет на экспрессию гена grim, дополнительный синтез NO нейтрализует антиапоптическое действие БТШ70 и увеличивает уровень экспрессии grim. Таким образом, мы предполагаем наличие конкурентной взаимосвязи между антиапоптической функцией БТШ70 и про-апоптическим действием оксида азота.